Features contributing to the genuineness of portraits on banknotes - Masuda, Osamu; Pedersen, Marius; Hardeberg, Jon Y. (Journal of Print and Media Technology Research, 2023)
Portraits have been thought to be one of the most important security features on banknotes for a long time. Portraits are often printed as the main feature of banknotes at a very high resolution in intaglio press. We tried to investigate on how important portraits actually are and what factors were contributing to the perceived genuineness of portraits on banknotes with a psychometric experiment. Banknotes were presented to subjects, enclosed in envelopes to cover the area other than the portrait, and the genuineness of those banknotes were rated. The factors affecting the rating were asked to the subjects at the same time. It was suggested that natural wear and tear strengthen the perceived genuineness of tested banknotes. Even though the inspection of the banknotes was restricted to on and around the portrait, the importance of the portrait was not high compared to other features, and a significant fraction of subjects answered that they paid no attention to any part of the face, which requires reflection and reconsideration of the use of human portraits as a security feature.